Ionic liquids and deep eutectic solvents and their potential use in production of sodium / Fatemeh Saadat Ghareh Bagh - Fatemeh, Saadat Ghareh Bagh (2014)
Sodium metal is an essential reducing agent, and it has a wide range of applications. In the present study ionic liquids (ILs) and their analogues known as deep eutectic solvents (DESs) have been proposed as electrolytes for sodium metal production at moderate temperatures of 90ºC to 150ºC. These electrolytes can be recognized as “green” solvents as they can potentially replace hazardous and polluting organic solvents. In using ILs or DESs as electrolytes for the production of sodium, three factors are of paramount importance: the solubility of commercially available sodium salts in the IL or DES, the conductivity of the solution of sodium salt in IL or DES, and the stability of the sodium metal in the IL or DES. DESs possess additional advantages over ILs especially because of the ease of synthesizing them and due to the lower cost of preparation. The evaluation of DESs as new electrolytes requires an insight of their main physical properties. For this purpose, some physical properties of specially-prepared DESs were measured and the results were reported. Zinc chloride-based DESs were characterized for their melting temperatures, viscosities, electrical conductivities and refractive indices. Subsequently, the solubility of different commercially available sodium salts were measured in different DESs and ILs at different temperatures. The solubility of sodium chloride increased with temperature in all the investigated ILs. The chemical structure of cations and anions in the ILs affected the solubility. The effect of the cation was larger than that of the anion.Different DESs were prepared by mixing ammonium or phosphonium salts, with different hydrogen bond donors (HBDs), or metal halides at several molar ratios. The effect of temperature on the solubility of sodium salts was found to be different from one DES to another. In certain DESs, the solubility of sodium salts increased with increasing temperature. The constituents of the DES and the molar ratios affected the solubility of sodium salts. DESs based on HBDs had very low solubility of NaCl in comparison to those that used metal halides as complexing agents. Sodium metal reacted with DESs containing HBDs; however, sodium metal was stable and did not react with DESs synthesized by utilizing metal halides. NRTL model was used to correlate the solubility of NaCl in some ILs as well as DESs at different temperatures. In most cases the experimental and calculated solubilities for NaCl in DESs and ILs were in good agreement. Cyclic voltammetry analysis was used to study the stability of sodium within the potential range found for metal halide-based DESs at different salt:metal halide molar ratios under different temperatures. It was found that the electrical windows of DESs droped with the increase in ZnCl2 molar composition in the DES and increased as the temperature increased. Reduction peak was observed for sodium ion in some ZnCl2-based DESs at certain temperatures. This work shows that DESs are superior to conventional molten salt electrolytes of Downs Process for the production of sodium metal due to lower operational temperature and less negative effects on the environment.